Development of tailored hydrogels using RAFT polymerization in continuous flow microreactor - Machado, Carla (2014)
This research is devoted to the development of tools aiding the production of smart hydrogels with tailored molecular architecture and properties. Molecular imprinting, RAFT polymerization and operation in continuous flow microreactor are individually considered and also simultaneously combined in order to try the synthesis of materials with improved performance.